Pengaruh Lama Penyimpanan Biji Kopi Liberika pada Suhu Kamar terhadap Mutu Mikrobiologis dan Kadar Okratoksin A: The Effect of Storage Time of Liberica Coffee Beans at Room Temperature on Microbiological Quality and Ochratoxin A Levels - Ramadani, Mutiara Bintang; Dewi Mustikaningtyas; Siti Harnina Bintari; Pramesti Dewi (Life Science, 2025)
Liberica coffee is one of the leading commodities in several regions so it has quite high economic potential. Coffee beans can be stored for quite a long time, more than one year, even more than 4 years before going through the roasting process. However, during long storage periods coffee beans can be attacked by microorganisms such as mold (ochratoxigenic and non-ochratoxigenic). This research aims to determine the effect of storage time on the quality of Liberica coffee beans, both microbiologically and chemically. The benefit of this research is to provide information on the quality of Liberica coffee beans. This research is a laboratory experimental research. The long storage time for coffee beans was 36 and 39 weeks. The results of the research showed that the yeast mold rate (AKK) on Liberica coffee beans stored for 39 weeks was greater than those stored for 36 weeks. The increase in AKK during storage is thought to be due to the presence of insects, temperature and humidity factors. A total of three mold isolates were found at week 36 and there were six mold isolates at week 39. The percentage of fungal isolate attacks at both weeks 36 and 39 was dominated by fungi of the Mucorales order (Mucor sp. and Absidia sp.). In the 36th week the attack of Mucor sp. amounted to 36.67% while in the 39th week the Mucor sp attack. 20%. and Absidia sp. 23.33%. Ochratoxin A (OTA) levels from week 36 to week 39 did not increase but instead decreased. This occurs due to OTA degradation by ochratoxin-degrading molds which are thought to be Aspergillus sp. during storage.